Comparison of performance of Xamarin and Flutter cross-platform frameworks - Piotr Kowalczyk; Mariusz Dzieńkowski (Journal of Computer Sciences Institute)
This article conducts a performance comparative study of two cross-platform development frameworks: Flutter and Xamarin. For this purpose, two test applications running on Android were developed, implementing the same functions, i.e. CRUD operations on the database and sorting an array of objects by the Merge Sort algorithm. Tests were performed on an emulator and on a physical device. The sorted arrays had different sizes, and database operations were performed for different sizes of data sets. The metric used for comparisons was the average implementation time of a given operation. The analysis of the research results showed that Xamarin was definitely more efficient in three CRUD operations, while Flutter performed computational operations, which in this case was sorting, much faster.